2016
DOI: 10.1016/j.inffus.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

The fusion process of interval opinions based on the dynamic bounded confidence

Abstract: In this paper, we propose a novel opinion dynamics model that is based on bounded confidence and termed interval opinion dynamics with the dynamic bounded confidence. In this opinion dynamics model, the agents express their opinions in numerical intervals, and the bounded confidences vary in a specified interval as time varies (i.e., dynamic bounded confidence). Based on several theoretical analyses of the proposed opinion dynamics, we propose conditions that are sufficient to form a consensus or fragmentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Opinion dynamics has been explored by most scholars in recent years [51][52][53]. However, few researchers explored the opinions of affinity and social noise systematically.…”
Section: Discussionmentioning
confidence: 99%
“…Opinion dynamics has been explored by most scholars in recent years [51][52][53]. However, few researchers explored the opinions of affinity and social noise systematically.…”
Section: Discussionmentioning
confidence: 99%
“…For each of the three parameters above, we evaluated how they influence the speed of convergence. So given a model with all parameters specified, we use to represent the average number of iterations needed to achieve convergence (see [ 50 ] for more details). Moreover, in order to observe convergence in a convenient way, we used an additional parameter which means the number of iterations we perform in a particular run.…”
Section: Simulations With Poe Modelmentioning
confidence: 99%
“…Group polarization is a hot topec in recent research of opinion dynamics [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In this section, we propose three extensions of our POE model which served for polarization.…”
Section: Three Mechanisms For Polarizationmentioning
confidence: 99%
“…In addition, some scholars have also considered the changes in the time when studying the convergence of models [17,18]. Some scholars combine opinion leaders [19][20][21], network media [22,23], information content [24], opinion form [25,26], and network structure [27,28] with the bounded con dence model to enrich the application of the bounded con dence model. For example, Chen et al suggested that leaders' opinions are important in guiding normal individuals to access truth, and that in some cases, small changes in parameters about individual characteristics can lead to large-scale changes in social groups.…”
Section: Introductionmentioning
confidence: 99%